2015
DOI: 10.1111/papr.12362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyaluronidase Addition to Lidocaine for Trigger Point Injection in Myofascial Pain Syndrome

Abstract: There were no significant differences between groups in terms of VNRS, NDI, or BPI-SF scores. However, TPI consisting of lidocaine mixed with hyaluronidase worked more effectively than lidocaine alone on post-TPI day 1. Further, hyaluronidase showed a tendency to reduce TPI-related soreness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This can result in dysfunctional deep fascial planes gliding over each other and over muscle, which predicts the basis of MFP 11 . In a randomized, double‐blind study following 61 adults with MFP of trapezius muscles for 14 days post trigger point injection (TPI), it was found that adults who received TPI with hyaluronidase/lidocaine had better post TPI soreness than those who only had lidocaine TPI 45 . Another randomized single‐blind study of patients with trapezius MFP showed that hyaluronidase TPI was superior to bicarbonate and lidocaine in reducing visual analogue scale 4 weeks after the injections 46 …”
Section: Hyaluronan and Painmentioning
confidence: 99%
“…This can result in dysfunctional deep fascial planes gliding over each other and over muscle, which predicts the basis of MFP 11 . In a randomized, double‐blind study following 61 adults with MFP of trapezius muscles for 14 days post trigger point injection (TPI), it was found that adults who received TPI with hyaluronidase/lidocaine had better post TPI soreness than those who only had lidocaine TPI 45 . Another randomized single‐blind study of patients with trapezius MFP showed that hyaluronidase TPI was superior to bicarbonate and lidocaine in reducing visual analogue scale 4 weeks after the injections 46 …”
Section: Hyaluronan and Painmentioning
confidence: 99%
“…Although pain related to the injection of normal saline is more than local anesthesia, the results of some studies indicate more pain related to injection, but findings are controversial ( 8 - 10 ). Cho et al investigated the injection of a combination of hyaluronidase and lidocaine on myofascial pain ( 11 ). Findings showed that injection of a combination of hyaluronidase and lidocaine is more effective than lidocaine alone.…”
Section: Introductionmentioning
confidence: 99%